Nómos and Díke in Plato's Laws - Cunha, Silvia Barros da (Revista Archai, 2026)
In the Laws, Plato revised the political project of the Republic, dependent on the figure of the philosopher-king. Having abandoned, in old age, the belief in individual virtue, he based his final political proposal on the legal norm, conceived as a collective expression of the rationality common to humankind and the cosmos. To develop this conception of law, Plato sought inspiration from the notion of cosmic justice of the first Ionian philosophers, and from Heraclitus in particular. In the Laws, Plato states that, due to the rationality that governs the cosmos, everything is always directed towards the good of the whole, and justice in the human sphere is the result of a law of attraction. By such law, the unjust man is attracted to where injustice prevails, and the just man to where justice overcomes. With this formulation of the problem of evil, the punishment of the wicked does not require the belief in the survival of the individual soul and a post-mortem judgment of the soul.